Bacterial nanocellulose (BNC) produced from sorbitol as a sustainable nano-filter for oil-water separation - Jagtap, Ashish; Krushnatray, Ajinkya; Dastager, Syed G. (International Journal of Biological Macromolecules, 2025)
Oil spillage is one of the serious problems for sustainable environment. Bacterial nanocellulose (BNC), a hydrophilic and highly porous material holds a promising material for oil-water separation from contaminants. In the present work, a hydrophilic BNC produced from a sorbitol as the carbon source demonstrated the unique porous symmetrical arrangement having an oleophilic property. The BNC membrane obtained showed the highest water holding capacity (WHC) of approximate to 147 gg 1 . The Brunauer-Emmett-Teller (BET) analysis of BNC revealed the unique characteristics of isothermic patterns, having macro sized pores with diameter of 121.3 nm and surface area of 40.6m2/g, which plays a vital role in separation of oil from water by allowing passage of only water through it. The separation efficiency of BNC membrane produced after 5th day of incubation has showed 99.0 % oil removal compared to 10 and 15th day incubated BNC membranes. a CFD model to investigate the possibilities of BNC membranes and clarify the dynamics of oil-water separation. The nanostructured network of BNC offers a tortuous path for oil molecules while allowing rapid permeation of water, leading to high separation selectivity and flux. Although BNC has been previously studied for oil water separation, this study provides new insights into the use of wet BNC membranes into its pristine state with sorbitol as carbon source for this application.
Keywords: bacterial nanocellulose; Macro porous; Oil-water separation; Sorbitol